Understanding Ultrasound Power Doppler Synovitis at Clinically Quiescent Joints and Thermographic Joint Inflammation Assessment in Patients with Rheumatoid Arthritis - York Kiat Tan; Julian Thumboo (Diagnostics)
Background/Objectives: Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory arthritis. We aim to study subclinical PD synovitis and thermographic joint inflammation assessment in patients with RA. Methods: We compared (1) PD synovitis at clinically quiescent (non-swollen; non-tender) joints based on patients’ disease activity and (2) thermography (hands/wrists) outcomes based on PD joint inflammation findings and patient’s disease activity. Results: Among eighty RA patients (mean (SD) age 57.0 (12.6) years; 61 of whom (76.3%) were female), the wrists (62.7%), second metacarpophalangeal joints (MCPJs) (37.0%), third MCPJs (33.8%), fourth MCPJs (24.8%), and fifth MCPJs (20.9%) were the five joint sites most frequently displaying subclinical PD synovitis; with no statistically significance differences (p > 0.05) between patients with 28-joint disease activity score (DAS28) < 3.2 versus those with DAS28 ≥ 3.2. At these five joint sites bilaterally, (1) the total maximum (Total Tmax), total average (Total Tavg), and total minimum (Total Tmin) temperatures were significantly greater (p < 0.05) for Total PD (TPD) score >1 versus TPD score ≤ 1, while their area under the ROC curve (AUC) values in identifying TPD score >1 ranged from 0.789 to 0.810, and (2) Total Tmax, Total Tavg, Total Tmin, and TPD score were significantly greater (p < 0.05) for patients with DAS28 ≥ 3.2 versus those with DAS28 < 3.2. Conclusions: Our results would serve as useful background data in studies on RA monitoring strategies detecting subclinical PD synovitis. Thermographic temperatures were greater in patients with greater disease activity and can help discriminate ultrasound PD joint inflammation severity.